If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -25 = 2x + 2 Reorder the terms: -25 + 3x = 2x + 2 Reorder the terms: -25 + 3x = 2 + 2x Solving -25 + 3x = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -25 + 3x + -2x = 2 + 2x + -2x Combine like terms: 3x + -2x = 1x -25 + 1x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -25 + 1x = 2 + 0 -25 + 1x = 2 Add '25' to each side of the equation. -25 + 25 + 1x = 2 + 25 Combine like terms: -25 + 25 = 0 0 + 1x = 2 + 25 1x = 2 + 25 Combine like terms: 2 + 25 = 27 1x = 27 Divide each side by '1'. x = 27 Simplifying x = 27
| -8x+4(x+2x-8)=-12 | | 0.4(x-3.5)=5.8x+1.84 | | 5/2a-5=30 | | 3x^8+30x^7+48x^6=0 | | (5-11i)-(-7+5i)= | | 75*60=95*40x | | .5w+5=13 | | (-3)=(-5)-x | | 2x-2[8(x+4)-(x-4)]-2= | | 8h-13-h=4-27h-2 | | 7-12x-5-2x=4 | | 93.96=4.7*p+8.7*p-2.6*p | | (-3)(14)(1.8)= | | 17615+550p=0 | | -42x^2-57x+120=0 | | 6-8(n-5)=6(-8n+2)-6 | | .75k+9=6 | | 11=[m+7] | | (81)^3/4 | | (-4)-x=6 | | (81)^(-3/4) | | 93.96=4.7*p+8.7*p-.6*p | | 3x+6-2x+8=24 | | 4/s–3=-2/5 | | (2x-3)-2(-x+4)=4x-11 | | 4/3y-16=-40 | | N*0.2=25 | | -(-7v+7)-2(v+4)=4v-4v | | 7x-8=8x-9 | | 1.7-11n=-10.7n+2.21 | | 9/5m-10=8 | | x-(-9)=-13 |